Nutrition and Food Supplies - Standing Joint Committee of Industrial Women's Organisations (London : The Labour Party)
1936-09 1936 1930s 33 pages : illustration not know, and it would be useful to know, whether the consumption of bread (and flour) was maintained throughout the period, whether potatoes were substituted for bread because of the substantial reduction in price, or whether potatoes were substituted for other foodstuffs because of the urgent need of the amount saved by such substitution for general household requirements. The official report points out that the experiment did not include any investigation of the influence on the general diet of the additional potatoes consumed, and states “General enquiries elicited the almost universal reply that no change had occurred except the additional consumption of potatoes, and in no case was mention made of a reduction of protein foods.” This does not carry us far as the lack of protein foods — especially first-class proteins — in the dietary of the unemployed, allows little margin for reduction. It is far more important to know how far one “filling” food took the place of another. But even if there were little substitution of potatoes for bread, it is not desirable from the point of view of health to increase the consumption of “filling” foods while essential body-building and protective foods are lacking. The case for stimulating a considerable increase in the consumption of potatoes by the unemployed has not been made; what is proved is that at the lowest income levels, the saving of a few coppers per week in any direction becomes a matter of great urgency. Beef The restriction of imports already referred to has not resulted in better prices for the home producer, because home and imported beef compete only to a limited extent. Those who can afford it, buy British beef, but if imports were shut out altogether the market for home beef would not improve while the incomes of the mass of the people remain at the present low level. Since September, 1934, farmers have received a subsidy from the Exchequer — amounting to £3,674,000 in 21 127/NU/5/5/1/12